2018
DOI: 10.1039/c8ra04949a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcination and pretreatment temperatures on the catalytic activity and stability of H2-treated WO3/SiO2 catalysts in metathesis of ethylene and 2-butene

Abstract: The effects of calcination and pretreatment temperatures of the H 2 -treated WO 3 /SiO 2 catalysts in metathesis of ethylene and 2-butene to propylene were investigated. The results showed that pretreatment with pure hydrogen over the non-calcined catalysts resulted in higher activity and stability than the calcined catalysts, and the hydrogen pretreatment temperature at 650 C offered the highest 2-butene conversion and propylene selectivity. The calcination of the catalyst before hydrogen pretreatment was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, the effect of H 2 was shown to be beneficial for Met catalysts operation, so its separation from the gas feed is not an added value. 106 For example, H 2 was found to lower coke deposition and increase the number of reduced catalytic active sites in ReO x catalysts. 56 A remarkable drawback of the separate reactors mode is that the PDH reaction runs independently of the Met reaction, and thus there is no shift in the PDH thermodynamic equilibrium, as discussed in Section 3.…”
Section: Catalysts Challenges and Opportunities In The Pto Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the effect of H 2 was shown to be beneficial for Met catalysts operation, so its separation from the gas feed is not an added value. 106 For example, H 2 was found to lower coke deposition and increase the number of reduced catalytic active sites in ReO x catalysts. 56 A remarkable drawback of the separate reactors mode is that the PDH reaction runs independently of the Met reaction, and thus there is no shift in the PDH thermodynamic equilibrium, as discussed in Section 3.…”
Section: Catalysts Challenges and Opportunities In The Pto Technologymentioning
confidence: 99%
“…Pre-treatments under inert or reducing conditions (e.g., He, H 2 or alkanes) have been shown to favor the formation of the active sites by removing strongly bound oxygen. [104][105][106] This has direct implications on the way the catalyst should be activated and regenerated during PTO, as discussed in Section 4.3.…”
Section: Metathesis Catalysts Overviewmentioning
confidence: 99%
“…The band at 225 nm attributed to isolated tetrahedral ([WO 4 ] 2− ) species involved the ligand-to-metal charge transfer, while the band at 262 nm referred to octahedral polytungstate ([WO 6 ] n− ) species involved O 2− → W 6+ charge transfer. 33,34 The absorption band up to 480 nm was assigned to bulk WO 3 species. 35 The impregnated W/SSP shows higher band intensities of octahedral polytungstate at 262 and bulk WO 3 at 480 nm compared with incorporated W-SSP, which is consistent with TEM, XRD, and Raman results.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…All the experiments were performed at optimized conditions (0.3 g of catalyst dosage, 0.4 ml of H 2 O 2 , pH 5, 100 ppm of pollutant concentration, 200 ml of sample volume) with respect to different temperature and time using different percentages of iron-loaded black soil. Few researchers reported that calcination can be used to remove volatile matter and impurities in catalyst synthesis, while few scientists reported that it can also be used to form high surface area or active sites (Gayapan, Sripinun, Panpranot, Praserthdam, & Assabumrungrat, 2018). Basically, calcination gives the strength and rigidity to the catalyst (Wang, Chen, Zhao, & Xu, 2017).…”
Section: Effect Of Calcination and Aging On Decolorization Of Mixed Dyementioning
confidence: 99%